Identification of a Lycopene β-Cyclase Required for Bacteriorhodopsin Biogenesis in the Archaeon Halobacterium salinarum - Peck, Ronald F. (American Society for Microbiology, 2002)
Biogenesis of the light-driven proton pump bacteriorhodopsin in the archaeon Halobacterium salinarum requires coordinate synthesis of the bacterioopsin apoprotein and carotenoid precursors of retinal, which serves as a covalently bound cofactor. As a step towards elucidating the mechanism and regulation of carotenoid metabolism during bacteriorhodopsin biogenesis, we have identified an H. salinarum gene required for conversion of lycopene to β-carotene, a retinal precursor. The gene, designated crtY, is predicted to encode an integral membrane protein homologous to lycopene β-cyclases identified in bacteria and fungi. To test crtY function, we constructed H. salinarum strains with in-frame deletions in the gene. In the deletion strains, bacteriorhodopsin, retinal, and β-carotene were undetectable, whereas lycopene accumulated to high levels (≈1.3 nmol/mg of total cell protein). Heterologous expression of H. salinarum crtY in a lycopene-producing Escherichia coli strain resulted in β-carotene production. These results indicate that H. salinarum crtY encodes a functional lycopene β-cyclase required for bacteriorhodopsin biogenesis. Comparative sequence analysis yields a topological model of the protein and provides a plausible evolutionary connection between heterodimeric lycopene cyclases in bacteria and bifunctional lycopene cyclase-phytoene synthases in fungi.